2013
DOI: 10.1245/s10434-013-3316-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Neoadjuvant Chemoradiotherapy on Postoperative Course after Curative-intent Transthoracic Esophagectomy in Esophageal Cancer Patients

Abstract: We observed an increase of cardiopulmonary complications in the neoadjuvant CRT group, without any effect on hospital or intensive care unit stay and mortality. Further research is warranted on the limitation of chemoradiation-induced cardiopulmonary toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 30 publications
5
45
0
Order By: Relevance
“…[13] Many reports comparing neoadjuvant chemoradiotherapy to upfront esophagectomy have been conflicting, with some institutions reporting increased rates of pneumonia, arrhythmias, sepsis, and respiratory failure, while others have reported no difference in postoperative complications. [1416] Of note, a retrospective analysis at MD Anderson identified that the likelihood of thirty-day pulmonary and gastrointestinal postoperative complications following esophagectomy increased two- to threefold for patients that received 3-dimensional conformal radiation therapy (3D-CRT) when compared to those neoadjuvant chemoradiation patients that received either intensity modulated radiation therapy (IMRT) or proton beam therapy (PBT), respectively. [17] While the NCDB does not capture specific postoperative complications, we found no significant difference in inpatient length of stay, thirty-day readmission, thirty-day mortality, or ninety-day mortality by neoadjuvant therapy type.…”
Section: Discussionmentioning
confidence: 99%
“…[13] Many reports comparing neoadjuvant chemoradiotherapy to upfront esophagectomy have been conflicting, with some institutions reporting increased rates of pneumonia, arrhythmias, sepsis, and respiratory failure, while others have reported no difference in postoperative complications. [1416] Of note, a retrospective analysis at MD Anderson identified that the likelihood of thirty-day pulmonary and gastrointestinal postoperative complications following esophagectomy increased two- to threefold for patients that received 3-dimensional conformal radiation therapy (3D-CRT) when compared to those neoadjuvant chemoradiation patients that received either intensity modulated radiation therapy (IMRT) or proton beam therapy (PBT), respectively. [17] While the NCDB does not capture specific postoperative complications, we found no significant difference in inpatient length of stay, thirty-day readmission, thirty-day mortality, or ninety-day mortality by neoadjuvant therapy type.…”
Section: Discussionmentioning
confidence: 99%
“…They retrospectively compared 96 patients treated with preoperative CRT (41.4 Gy/carbo/taxol) with matched controls who were treated with surgery only [20]. In this study, rates of pneumonia, cardiac arrhythmia and pleural effusion were observed more frequently in the preoperatively treated group.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies [13][14][15]25 and reviews 5,26 have investigated the influence of NCRT on AL in EC, and conflicting data have emerged. This is so for several reasons: the studies are underpowered to study such a rare event, some were not designed to study the incidence of AL, the surgical techniques used vary widely, and in some studies groups are not comparable.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Despite this, AL remains an important cause of patient morbidity and impaired quality of life. [6][7][8][9] Although the evidence that neoadjuvant chemoradiotherapy (NCRT) provides a survival benefit in EC is increasing, 10,11 there is still some controversy on its impact on AL, [12][13][14][15] with some trials having shown a deleterious impact 16 and others not. These include both patient and tumoral characteristics [an American Society of Anesthesiologists (ASA) score of ≥III, malnutrition, cardiovascular disease, tobacco consumption, steroid use, chronic renal failure, and tumoral location] and perioperative factors (cervical or hand-sewn anastomosis, positive longitudinal resection margins, and operative time >5 hours) as also administration of neoadjuvant therapy.…”
mentioning
confidence: 99%